2002
DOI: 10.1074/jbc.m111813200
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-trp RNA-binding Attenuation Protein (Anti-TRAP), AT, Recognizes the Tryptophan-activated RNA Binding Domain of the TRAP Regulatory Protein

Abstract: In Bacillus subtilis, the trp RNA-binding attenuation protein (TRAP) regulates expression of genes involved in tryptophan metabolism in response to the accumulation of L-tryptophan. Tryptophan-activated TRAP negatively regulates expression by binding to specific mRNA sequences and either promoting transcription termination or blocking translation initiation. Conversely, the accumulation of uncharged tRNA Trp induces synthesis of an anti-TRAP protein (AT), which forms a complex with TRAP and inhibits its activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
61
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 25 publications
5
61
0
Order By: Relevance
“…TRAP regulates the expression of tryptophan metabolism genes by transcription attenuation (trpEDCFBA operon) and translation control (trpG, trpP, ycbK, and trpE) mechanisms. rtpA encodes anti-TRAP (AT), a protein that binds to and inactivates tryptophan-activated TRAP (25). PLK.…”
Section: Methodsmentioning
confidence: 99%
“…TRAP regulates the expression of tryptophan metabolism genes by transcription attenuation (trpEDCFBA operon) and translation control (trpG, trpP, ycbK, and trpE) mechanisms. rtpA encodes anti-TRAP (AT), a protein that binds to and inactivates tryptophan-activated TRAP (25). PLK.…”
Section: Methodsmentioning
confidence: 99%
“…Expression of the at operon is controlled by tandem transcription and translation regulatory mechanisms based on sensing the level of charged͞uncharged tRNA Trp (17). Transcription of the structural genes of the at operon is regulated via the T-box transcription antitermination mechanism, where elevated levels of uncharged tRNA Trp induce transcription of rtpA (18), leading to AT production and increased trp operon expression and tryptophan biosynthesis (19). Translational control of at operon expression is provided by the ability of a translating ribosome to move along the mRNA region encoding a tryptophan-rich leader peptide.…”
mentioning
confidence: 99%
“…In TRAP͞RNA complexes, the 11 (G͞U)AG repeats of the RNA chain bind to 11 binding sites on the surface of the protein and form a belt around the protein ring (23)(24)(25). A study with mutant TRAP proteins revealed that AT forms a complex only with tryptophan-activated TRAP and appears to recognize a region that is also involved in RNA binding (19). These observations led to the proposal that AT prevents the TRAP͞RNA interaction by masking RNA-binding sites of TRAP (19).…”
mentioning
confidence: 99%
See 2 more Smart Citations